Emotion and the researcher : sites, subjectivities, and relationships - Loughran, Tracey; Mannay, Dawn (Studies in qualitative methodology ;, 2018)
Traditional research discourses continue to present academic work as rational, detached, objective and free from emotion. This volume argues that the presentation of research as objective conceals the subject positions of researchers, and the emotional imperatives that often drive research. The collection engages with the emotional experiences of researchers working in different traditions, contexts and sites, and demonstrates their centrality in data production, analysis, dissemination and ethical practice. This edited volume offers contributions from a range of well-established and early career scholars who argue for an emotional rebellion in the academic world. The authors reflect on their own experiences of research, generously sharing their approach to their craft, and the uncertainties, concerns, enjoyments, and questions it entails. The contributors are based in a range of disciplines across the humanities, social sciences and STEM, and in the museum sector. This provides a unique opportunity for reflection on differences between and similarities across disciplinary boundaries, shedding new light on common problems and opportunities stimulated by emotion in research. The collection demonstrates how emotion can be valuable and meaningful in the activities of research, reflection and dissemination: offering authenticity to the academic voice, bringing clarity to interpretive biases, producing engaging outputs which connect with diverse readerships, and potentially reshaping disciplinary foundations and relations. Emotion and the Researcher: Sites, Subjectivities and Relationships will be an invaluable companion for researchers, postgraduate students and other academics with an interest in the emotional elements of conflict, negotiation, relationality and reflexivity, within and beyond the research encounter.